Persepsi guru mengenai kurikulum merdeka di sekolah dasar - Hemaswitary, Kartika Chandra; Mahfud, Hasan; Supianto, Supianto (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
The goal of this study is to learn how the autonomous curriculum being used in Indonesia is seen by the instructors at SD N Tunggulsari II. Descriptive techniques are used in this study's qualitative methodology. Five instructors from SD N Tunggulsari II served as the study's subjects. Interviews, observation, and documentation are used for data collection. Sugiyono's theory, which encompasses data reduction, data presentation, and conclusionmaking, is used in data analysis. The study's findings show that teachers have a positive opinion of the autonomous curriculum, but there are still many areas that need to be changed in order for it to be used more successfully.